Ants Visiting the Post-Floral Secretions of Pericarpial Nectaries in Palicourea rigida (Rubiaceae) Provide Protection Against Leaf Herbivores But Not Against Seed Parasites - Kleber Del-Claro; Rhainer Guillermo-Ferreira; Helena Zardini; Elizângela Machado Almeida; Helena Maura Torezan-Silingardi (Sociobiology)
Pericarpial nectaries (PNs) have frequently been treated in the literature as extrafloral nectaries (EFNs). This treatment is partly justified by their morphological and functional similarities in attracting bodyguard ants to protect the plant against herbivores. Palicourea rigida is a common Neotropical savanna treelet with tubular yellow flowers that are pollinated by hummingbirds. After pollination, the corolla falls, but the sepal ring remains and keeps the nectaries active over the ovarium throughout fruit development stages. Using a standard ant-exclusion experiment, we tested whether these PNs attract ants to protect the developing fruits against seed parasites and the leaves against chewing herbivores. We analyzed the differences between the initial and final leaf area. Before full fruits maturity, they were collected and taken to the laboratory for weighing and to observe wasp emergence. The number of wasps per fruit and per plant was recorded. The results showed that after pollination, the floral nectaries of P. rigida act as EFNs, attracting visiting ants. Ant-tended plants lost significantly less leaf area and had heavier fruits than untended plants. However, the ants did not protect the fruits against seed-parasitic wasps. In P. rigida, the post-floral secretions of PNs play the same role as EFNs, and the ant-plant mutualism is context-dependent based on the type of herbivore and the plant tissue consumed.